The Role of Porphyromonas gingivalis Outer Membrane Vesicles in Periodontal Disease and Related Systemic Diseases - Zhang, Zhiying; Liu, Dongjuan; Liu, Sai; Zhang, Shuwei; Pan, Yaping (Frontiers in Cellular and Infection Microbiology, 2021)
Periodontal disease is a chronic infectious disease associated with a variety of bacteria, which can cause damage to the periodontal support structure and affect a variety of systemic system diseases such as cancer, cardiovascular disease, diabetes, rheumatoid arthritis, non-alcoholic fatty liver, and Alzheimer's dsease. Porphyromonas gingivalis (P. gingivalis) is the most important pathogenic bacteria for periodontal disease. It can produce outer membrane vesicles (OMVs) and release them into the environment, playing an important role in its pathogenesis. This article focuses on P. gingivalis OMVs, reviews its production and regulation, virulence components, mode of action and related diseases, with a view to providing new ideas for the prevention and treatment of diseases related to P. gingivalis infections.